2019
DOI: 10.5194/hess-2019-213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating water flux and evaporation losses using stable isotopes of soil water from irrigated agricultural crops in tropical humid regions

Abstract: Abstract. Reliable information on water flow dynamics and water losses via irrigation on irrigated agricultural fields is important to advance water management strategies. We investigated the effect of season (wet season, dry season), irrigation management (flooded, non-flooded), and crop diversification (wet rice, dry rice, and maize) on soil water dynamics and water losses via evaporation during plant growth. Soil water was extracted and analyzed for the stable isotopes of water (δ2H and δ18O), and the fract… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Vegetation types therefore have a dominant impact on soil water movement. Amani et al [63] also confirmed the influence of vegetation and field conditions on the variability of soil water flow mechanisms. In addition, the slope and intercept of the SWL in the wild grassland were higher than those of the arbor and shrub forests; this suggests that precipitation was the dominant supply of soil water in the grassland, while early soil water predominantly replenished soil water in the arbor land and shrubland.…”
Section: Influence Of Stand Type On Soil Water Stable Hydrogen and Oxygen Isotopesmentioning
confidence: 80%
“…Vegetation types therefore have a dominant impact on soil water movement. Amani et al [63] also confirmed the influence of vegetation and field conditions on the variability of soil water flow mechanisms. In addition, the slope and intercept of the SWL in the wild grassland were higher than those of the arbor and shrub forests; this suggests that precipitation was the dominant supply of soil water in the grassland, while early soil water predominantly replenished soil water in the arbor land and shrubland.…”
Section: Influence Of Stand Type On Soil Water Stable Hydrogen and Oxygen Isotopesmentioning
confidence: 80%
“…As the lc-excess is a more representative 280 indicator of evaporation than the single isotope system ( 8 O or 2 H) and the d-excess (Sprenger et al, 2017b;Masson-Delmotte et al, 2005), evaporation estimates from the new method should be more accurate. Moreover, similar to the d-excess method (Hu et al, 2018), the new method combines 2 H and 18 O, avoiding the inconsistency between the separate implementation of 2 H and 18 O in the Craig-Gordon method (Sprenger et al, 2017a;Mahindawansha et al, 2019). Overall, f estimation using the new method is more robust than the remaining two methods and would be widely 285 applicable.…”
Section: The Advantages Of Using Lc-excess To Quantitatively Estimate Fmentioning
confidence: 97%
“…Conversely, a relatively long-term f can be estimated using stable 2 H and 18 O isotopes, because they are only enriched dur-40 ing soil evaporation processes (Zimmermann et al, 1966) and can integrate soil evaporation processes occurring over interest of period (Jasechko et al, 2013;Allison and Barnes, 1983). The primary advantage is that it does not need continuous field observations with high frequency and have been used to estimate f in various studies (Allison and Barnes, 1983;Sprenger et al, 2017a;Hsieh et al, 1998;Mahindawansha et al, 2019). Previous studies commonly utilize the shallow soil water 2 H / 18 O isotopes; however, obtaining long-term average f requires continuous sampling effort of shallow soil 45 due to the strong isotopic dynamics in that part of the soil profile, which can be costly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Craig-Gordon model (C-G model), proposed by Harmon Craig and Louis Gordon [15], is a renowned isotopic model that explains the combined effect of equilibrium and kinetic isotopic fractionation during the phase transition from liquid water to vapor [16][17][18]. This model is commonly used to interpret and model the isotopic composition of oceans [19], lakes, atmospheric water, soil water, and other natural water systems [8,20,21]. It has become an important theoretical method for isotopic studies of the hydrological cycle, both regionally and globally.…”
Section: Introductionmentioning
confidence: 99%